Trapping and aerogelation of nanoparticles in negative gravity hydrocarbon flames - Chakrabarty, Rajan K.; Novosselov, Igor V.; Beres, Nicholas D.; Moosmüller, Hans; Sorensen, Christopher M.; Stipe, Christopher B. (My University, 2014)
We report the experimental realization of continuous carbon aerogel production using a flame aerosol reactor by operating it in negative gravity (−g; up-side-down configuration). Buoyancy opposes the fuel and air flow forces in −g, which eliminates convectional outflow of nanoparticles from the flame and traps them in a distinctive non-tipping, flicker-free, cylindrical flame body, where they grow to millimeter-size aerogel particles and gravitationally fall out. Computational fluid dynamics simulations show that a closed-loop recirculation zone is set up in −g flames, which reduces the time to gel for nanoparticles by ≈10[superscript 6] s, compared to positive gravity (upward rising) flames. Our results open up new possibilities of one-step gas-phase synthesis of a wide variety of aerogels on an industrial scale.
Keywords: Carbon aerogel production; One-step gas-phase synthesis; Aerogels